(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic generated a series of changes in the education format. This study aimed to verify the effects of the transition from classroom to online education on the quality of life, and anxiety of Brazilian teachers. Eighty teachers responded remotely, questionnaires to characterize the sample, perception of online teaching, quality of life, and anxiety. The results indicate the existence of indicators of agreement about knowledge to teach online, in the need to modify teaching methodology and that online education is more stressful. Indicators of disagreement that online education is the future of higher education and that students learn more in this model. When assessing the quality of life, men had better scores in the vitality, social aspect, limitation by physical aspect, and mental health domains. Individuals who do not have comorbidities had better scores for functional capacity, pain, and general health status. The group in social isolation had a lower score in social aspects. State anxiety was higher than trait anxiety. Anxiety levels were influenced by time of isolation and showed a negative correlation with the quality of life. The transition from to remote education affected the perception of teaching, quality of life, and anxiety of Brazilian teachers.